Reconstruction of Morality Offenses in the New Criminal Code: A Study of Article 412 from the Perspectives of Positive Law and Islamic Criminal Law - Fairuz Abdul Haq; Martin Rahmat Hidayat (Jurnal El-Thawalib, 2026)
Reconstruction of Morality Offenses in the New Criminal Code: A Study of Article 412 from the Perspectives of Positive Law and Islamic Criminal Law